Does Social Responsibility Affect Performance of Islamic Bank in Indonesia? The Role of Board Diversity - Maulida Nurul Innayah; Rifka Utami Arofah; Bima Cinintya Pratama (Universitas Negeri Semarang, 2023)
According to Islamic teachings, banking is expected to have social goodness, environmental concern, and ethical behavior. Islamic banking is a company that supports the smooth running of the economy; thus, Islamic banks are expected to be more socially responsible. This study examines the moderating effect of board diversity on the relationship between social responsibility and the performance of Islamic banking in Indonesia. The population in this study are Islamic banking companies in Indonesia whose data is obtained from the company's annual report. The sampling technique used in this study was purposive sampling. The sample in the study consisted of 136 firm-year observations for 16 registered Islamic banks in Indonesia. Using panel data regression testing, the results show that social responsibility positively affects the performance of Islamic banking in Indonesia. The results of this study are in line with stakeholder theory which explains that Islamic banking companies try to meet different stakeholder expectations, one of which is by carrying out Islamic social responsibility to increase stakeholder trust, which has an impact on improving firm performance. However, the results of this study found that female directors in Indonesia are a minority, so their existence cannot improve the management of social responsibility and performance of Islamic banking.